Fundamentals of production/operations management - Martin, Matt L. ([Place of publication not identifed] : Goodwill Book Store, 1996)
This book is written to address the long clamour to provide our faculty, students and non-technical professionals with reference material on this challenging subject which transcends cultural biases.
Introduction -- Process planning -- Capacity planning -- Forecasting -- Assembly line balancing -- Plant layout -- Plant locatio -- Total quality management -- Inventory management -- Operations scheduling
Keywords: OPERATIONS MANAGEMENT